Assessment of post-pandemic user expectations, satisfaction and intentions to use seating furniture in Nie Er Community Park, Yuxi City, China - Zhang, Ling (2023)
Seating furniture is essential for urban community parks. However, during the emergency of the COVID-19 pandemic, the traditional seating designs of community parks could not be adapted to users’ new requirements, highlighting the lack of a comprehensive framework to guide designers, policymakers, and managers in adapting to new user expectations. This situation is exacerbated by the insufficient research on seating furniture in the post-pandemic context. This study aims to develop a comprehensive framework to capture post-pandemic user expectations, satisfaction, and intentions regarding seating furniture to guide designers, policymakers, and managers to improve the user experience and thereby increase the utilization of public spaces in the post-pandemic era. Semi-structured interviews and observations were used to collect data on the factors related to expectations, satisfaction, and intention to use park spaces post-pandemic. Subsequently, a questionnaire survey was conducted with 426 community park visitors in Yunnan Province to measure the aforementioned variables, and structural equation modeling (SEM) was used to confirm the hypothesized relationships among them. Five main dimensions (function, appearance, material, safety features, space environment characteristics and location) were found to be the main factors influencing users’ expectations, satisfaction, and usage intentions regarding seating furniture. In addition, the results indicated that user satisfaction with park seating not only has a positive effect on intention to use the furniture but also mediates the relationship between user expectations and intention to use the furniture. Based on these findings, a comprehensive framework was developed and validated by experts to guide future design and management strategies for community park seating. This framework provides theoretical support for the design and management of seating furniture for urban community parks, which is essential for promoting park sustainability.